2001
DOI: 10.1136/thorax.56.7.529
|View full text |Cite
|
Sign up to set email alerts
|

Decreased bronchodilating effect of salbutamol in relieving methacholine induced moderate to severe bronchoconstriction during high dose treatment with long acting beta2 agonists

Abstract: Background-In vitro the long acting 2 agonist salmeterol can, in contrast to formoterol, behave as a partial agonist and become a partial antagonist to other 2 agonists. To study this in vivo, the bronchodilating eVect of salbutamol was measured during methacholine induced moderate to severe bronchoconstriction in patients receiving maintenance treatment with high dose long acting 2 agonists. Methods-A randomised double blind crossover study was performed in 19 asthmatic patients with mean forced expiratory vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
47
0
2

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(51 citation statements)
references
References 26 publications
2
47
0
2
Order By: Relevance
“…Compared to pre-treatment with placebo, there was a highly significant near-linear reduction in AUC0-40 FEV1 with b-agonist as bronchoconstriction increased (pv0.0001). Thus, the present study goes further than earlier investigations [12][13][14] by demonstrating that, in the same patient, the effects of pharmacological tolerance become increasingly apparent with increasing degrees of bronchoconstriction.…”
Section: Discussionmentioning
confidence: 43%
See 2 more Smart Citations
“…Compared to pre-treatment with placebo, there was a highly significant near-linear reduction in AUC0-40 FEV1 with b-agonist as bronchoconstriction increased (pv0.0001). Thus, the present study goes further than earlier investigations [12][13][14] by demonstrating that, in the same patient, the effects of pharmacological tolerance become increasingly apparent with increasing degrees of bronchoconstriction.…”
Section: Discussionmentioning
confidence: 43%
“…In both of these studies, measuring the response to b-agonist in the presence of methacholineinduced bronchoconstriction permitted the demonstration of tolerance which would not otherwise have been detected. These findings raise the possibility that the effects of tolerance to inhaled b-agonists may be further accentuated by bronchoconstriction beyond the 20% fall in FEV1 that was induced in these investigations [12][13][14]. In acute severe asthma, patients will usually have a reduction in their FEV1 that greatly exceeds 20%.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…In the current study, the effect of the treatment was evaluated two weeks after its conclusion, because another group of authors reported that there is a significant bronchodilating and bronchoprotective effect after two weeks of active treatment. (19) Patients with COPD and elevated IgE levels, atopy or sputum eosinophilia form a subgroup of patients with a better prognosis and a greater likelihood of corticosteroid responsiveness. (20) In our patients, we found no statistically significant difference between those with high serum total IgE and those with low serum total IgE in terms of the response to treatment.…”
Section: Resultsmentioning
confidence: 99%
“…The impact of these changes is yet to be explored, but it is likely that there are those that are detrimental in terms of the cellular or organ physiology in these two syndromes. Indeed, ␤-agonist use continues to be controversial in asthma, with multiple reports of increased mortality or other indices of poor asthma control during continuous (chronic) therapy (4,17,22,25). Given the efficacy of ␤-agonists for relieving bronchospasm, one strategy for new, combined, pharmacological therapy may involve an additional agent that inhibits dysregulation of certain transcription factors by ␤-agonists.…”
Section: Discussionmentioning
confidence: 99%